2021
DOI: 10.1186/s13102-021-00291-3
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic ankle supports effects on time to stabilization, perceived stability and ground reaction force during lateral landing in female collegiate athletes with chronic ankle instability

Abstract: Background This study was designed to investigate effects of Kinesiotape (KT) with closed basket weave method and lace-up braces (LB) on the vertical time to stabilization, peak vertical ground reaction force (PvGRF), and time to PvGRF as well as perceived stability during lateral landing of participants with chronic ankle instability before and after fatigue. Methods Thirty female college athletes with chronic ankle instability of three conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The findings of the present study demonstrated that KT significantly reduced peak vGRF. However, Yalfani et al [ 39 ] conducted ankle KT on patients with chronic ankle instability and found that vGRF during lateral landing tasks was significantly higher than that in the control group. The disparities in results could be related to variations in taping techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study demonstrated that KT significantly reduced peak vGRF. However, Yalfani et al [ 39 ] conducted ankle KT on patients with chronic ankle instability and found that vGRF during lateral landing tasks was significantly higher than that in the control group. The disparities in results could be related to variations in taping techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The Open-source software Python 3.8 was used to filter and calculate the original ground reaction force data, specifically using a second-order low-pass Butterworth filter with a cut-off frequency of 12Hz. 47 The TTS after landing was defined as the time for the vertical force component to reach and stay within 5% of the body weight. 48 …”
Section: Methodsmentioning
confidence: 99%
“…Landing has been recognized as one of the most common causes of non-contact ankle sprain and postural controlling after landing is one of the most important factors in preventing injury [ 8 ]. Some studies reported that the risk of ankle sprain in people with balance deficits is up to seven times higher than that in their healthy counterparts [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that the risk of ankle sprain in people with balance deficits is up to seven times higher than that in their healthy counterparts [ 9 ]. One of the important parameters of postural controlling during landing is the time to stabilization (TTS) [ 8 ]. TTS is a variable for measuring neuromuscular control [ 10 ], and vertical TTS (vTTS) refers to the time at which the vertical force of the ground after a dynamic disturbance is stabilized until the body reaches a steady posture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation